Sejarah Pemikiran Islam: Perkembangan Sistem Ekonomi dari Masa Ke Masa - Afiyah Zahrah; Fikriansyah Fikriansyah; Juwita Sifas Sembiring; Ahmad Wahyudi Zein (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The history of the development of the Islamic economic system has undergone significant transformations from the time of the Prophet Muhammad SAW to the modern era. In the early period, the Islamic economic system was based on Qur'anic principles such as justice, transparency, and the prohibition of interest (riba). The Prophet Muhammad SAW established the foundations of the economy, which included the management of zakat, waqf, and market oversight. The era of the Khulafa' al-Rashidin continued these policies with the management of the baitul mal and economic expansion through ijtihad. During the Umayyad and Abbasid periods, the economic system became more complex with the introduction of Arabic currency and innovative tax management. In the modern era, Islamic economics has experienced a revival through its integration into academia and the implementation of Shariah compliant financial institutions like Bank Muamalat.